2007
DOI: 10.1111/j.1365-313x.2007.03339.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular co‐localization of Arabidopsis RTE1 and ETR1 supports a regulatory role for RTE1 in ETR1 ethylene signaling

Abstract: Ethylene is an important plant growth regulator perceived by membrane-bound ethylene receptors. The ETR1 ethylene receptor is positively regulated by a predicted membrane protein, RTE1, based on genetic studies in Arabidopsis. RTE1 homologs exist in plants, animals and protists, but the molecular function of RTE1 is unknown. Here, we examine RTE1 expression and subcellular protein localization in order to gain a better understanding of RTE1 and its function in relation to ETR1. Arabidopsis plants transformed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
120
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 52 publications
4
120
0
5
Order By: Relevance
“…Genetic analysis indicates that AtRTE1 functions at or upstream of the ethylene receptors but acts independently of the RAN1 copper transporter (Resnick et al, 2006. In support of this hypothesis, AtRTE1 colocalizes with ETR1 in the ER and Golgi membranes and interacts with the N-terminal region of the ETR1 and ERS1 receptors (Zhou et al, 2007;Dong et al, 2008Dong et al, , 2010. Interestingly, mutations at the rte1 locus suppress ethylene insensitivity mediated by a subset of, but not all, etr1 mutant alleles, and reduced ethylene sensitivity mediated through AtRTE1 overexpression is primarily dependent on the presence of ETR1 and not the other ethylene receptors (Resnick et al, 2006Zhou et al, 2007).…”
supporting
confidence: 52%
See 3 more Smart Citations
“…Genetic analysis indicates that AtRTE1 functions at or upstream of the ethylene receptors but acts independently of the RAN1 copper transporter (Resnick et al, 2006. In support of this hypothesis, AtRTE1 colocalizes with ETR1 in the ER and Golgi membranes and interacts with the N-terminal region of the ETR1 and ERS1 receptors (Zhou et al, 2007;Dong et al, 2008Dong et al, , 2010. Interestingly, mutations at the rte1 locus suppress ethylene insensitivity mediated by a subset of, but not all, etr1 mutant alleles, and reduced ethylene sensitivity mediated through AtRTE1 overexpression is primarily dependent on the presence of ETR1 and not the other ethylene receptors (Resnick et al, 2006Zhou et al, 2007).…”
supporting
confidence: 52%
“…S1). The current model of the ethylene signaling pathway would place the localization of the receptors and their interaction with the GR/ RTE1 proteins within the ER, and previous studies have suggested either exclusive localization of AtRTE1, OsRTH1, and OsRTH2 within the Golgi or dual localization within the Golgi and ER (Zhou et al, 2007;Dong et al, 2008;Zhang et al, 2012). These slight discrepancies may be caused by the use of different experimental systems and high-level overexpression of heterologous transgenes that may influence the subcellular localization of proteins.…”
Section: Discrepancies In the Subcellular Localization Of The Gr/rte1mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, numerous studies have expanded the linear view of ethylene signaling pathway. For instance, a new protein, REVERSION-TO-ETHYLENE SENSITIVITY1 (RTE1), which is colocalized with the ethylene receptor ETR1, was identified as a positive regulator of ETR1 function, but the connection between RTE1 and ETR1 is still under investigation (Solano et al 1998;Resnick et al 2006;Dong et al 2008). Additionally, a number of groups found that post-transcriptional regulation of protein levels is a key mechanism of modulating EIN3 activity by ethylene.…”
mentioning
confidence: 99%